Growth and Yield Responses of Tomato (Lycorpersicon Esculentum Mill) to Trichoderma Inoculants in Soilless Medium - Ragai Kundat, Franklin (2002)
Growth and yield responses of tomato to Trichoderma inoculants in Soilless medium (mixture of coconut dust and peat) (Cdp) under Protected Environment Agriculture (PEA) system was attempted. Two Trichoderma species; T harzianum (UPM 29) and T. Virens (UPM 23) singly and as mixtures were used in the study. The physical, chemical and microbiological properties of Cdp was suitable for growth of tomato and proliferation and survival of Trichoderma. Cdp has good pore size with bulk density within the range of mineral soil (1.0 -1.8 g/l). Cdp has high water availability of 22.23%. However they has low microbial populations comprising of mainly the genera Aspergillus and Penicillium. The effect of soilless media on proliferation and survival of Trichoderma was carried out by either adding the inoculant as an additive to the soi11ess medium or as bioseed treatment. T. harzianum population in Cdp was reduced by 32% after 15 days of application. However, population for T Virens when applied singly or as mixtures of T. harzianum + T virens dropped at day 6 but remained stable thereafter until the end of the experiment. Trichoderma population was higher on the roots throughout the 21 days of experimental period, suggesting that Trichoderma can colonize the germinating roots and live on the root exudates. Application of Trichoderma as additives to the soilless medium was a better delivery method as it gave better distribution and easy contact with the growing roots. Therefore, application as additives to germination mixes was selected to evaluate the effect of air-dried preparation of Trichoderma inoculants on growth and yield responses of tomato.